Application of Module Structure to Coding Theory: A Systematic Literature Review - Faldiyan, Muhammad; Sylviani, Sisilia (Jurnal Matematika Integratif, 2025)
A systematic literature review is a research process that identifies, evaluates, and interprets all relevant study findings connected to specific research questions, topics, or phenomena of interest. In this work, a thorough review of the literature on the issue of the link between module structure and coding theory was done. A literature search yielded 470 articles from the Google Scholar, Dimensions, and Science Direct databases. After further article selection process, 14 articles were chosen to be studied in further depth. The items retrieved were from the previous ten years, from 2012 to 2022. The PRISMA analytical approach and bibliometric analysis were employed in this investigation. A more detailed description of the PRISMA technique and the significance of the bibliometric analysis is provided. The findings of this study are presented in the form of brief summaries of the 14 articles and research recommendations. At the end of the study, recommendations for future development of the code structure utilized in the articles that are further investigated are made